Kekerasan Fisik Terhadap Anak Pasca Pandemik Covid 19 - Margie Gladies Sopacua (Sawerigading Law Journal, 2023)
Children are a vulnerable group who need to receive protection from all acts of crime and violence in accordance with statutory provisions. Violence against children is not something new, this can be seen in the post-pandemic impact of Covid-19 which has also resulted in an increase in the number of acts of violence against children as can be seen from statistical data from the Women and Children Protection Unit (PPA) of the Ambon Island City Police and On the Lease Islands, there has been an increase in cases of physical violence against children, namely in 2020 there were 4 cases of reports submitted to the PPA Polresta, then in 2021 this increased to 10 cases against children in the form of physical violence. Forms of physical violence against children include pulling, kicking, hitting with their hands, pinching, punishing them until they fall ill or faint, hitting them with objects, and injuring them with dangerous objects. Efforts to Prevent Physical Violence Against Children Post the Covid-19 Pandemic; (1) Carrying out legal counseling to increase legal awareness and education about legal sanctions for children who commit physical violence; (2) provide outreach on the prevention of physical violence against children, as a joint effort to protect children. This effort is to share understanding with the community that children are a gift that should be protected and looked after (3) Make billboards related to stopping physical violence against children; and (4) the Women and Children Protection Unit (UPPA) collaborates with the Women's and Children's Empowerment Service in providing education to children, especially in the scope of education starting from elementary to high school regarding physical violence. To prevent physical violence against children, parents must be good examples as part of the smallest family for children to avoid physical violence. Apart from that, it is also hoped that law enforcement officials (police) will increase efforts to prevent physical violence against children after the Covid-19 pandemic